Environmental Impact of Pharmaceuticals and Personal Care Products - Amean A. Yasir (Journal of Global Pharma Technology, 2017)
Medical waste is considered to be a hazardous waste of a special nature due to its high toxicity and its toxic and radioactive chemicals and its ability to develop diseases. The extent of the presence of germs and viruses in the medical waste and the amount of dose and exposure method and the extent of resistance of the body to these microbes. Medical waste includes the waste of isolation rooms for patients with infectious diseases, residues of bacteria, infectious and biological agents, waste of sterilization, disinfection, blood, serums and plasma, and pharmaceutical residues. This guide provides an overview of hospital waste generating processes and presents options for minimizing waste generation through source reduction and recycling. Reducing the generation of these materials at the source, or recycling the wastes on or off site, will benefit hospitals by reducing disposal costs and lowering the liabilities associated with hazardous waste disposal. The hazardous wastes generated by general medical and surgical hospitals are small in volume relative to those of industrial facilities; however, the wastes are of a wide variety. Some of the hazardous materials used by hospitals that become part of their waste streams include chemotherapy and antineoplastic chemicals; solvents; formaldehyde; photographic chemicals; radionuclide’s; mercury; waste aesthetic gases; and other toxic, corrosive and miscellaneous chemicals. Additional wastes such as infectious waste, incinerator exhaust, laundry-related waste, utility wastes, and trash are not addressed in this guide. The results showed that most hospitals in Basra lack systematic application of the concept of solid waste management and lack of awareness among medical waste workers. All waste incinerators in hospitals are old, operate under temperatures of less than 400 ° C and are therefore a source of toxic gas emissions Dioxin Intermediates. Ashes of incinerators, which contain a percentage of toxic heavy metals and pathogens, are put into domestic waste in landfills and thus make its impact the environment is highly negative in terms of pollution and disease transfer. Misuse of residues with chemical drugs they are used to treat cancer patients and treat them as other medical waste, as exposure to such waste are very dangerous to workers because of their ability to kill human cells or cause malformation.Keywords:Medical waste, Hospital waste, Environmental pollution, Hazardous materials.